2017
DOI: 10.1136/sextrans-2017-053292
|View full text |Cite
|
Sign up to set email alerts
|

Individual and partnership factors associated with anticipated versus actual partner notification following STI diagnosis among men who have sex with men and/or with transgender women in Lima, Peru

Abstract: Anticipated notification imperfectly reflects actual PN behaviour. Future interventions to improve PN among MSM-TW in Peru need to acknowledge partnership contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Consequently, the data pointed to a higher probability of not getting casual sexual partners to come to the health unit, in comparison with that of noncasual ones. Similar results were described in a study on PR carried out in the United States, according to which patients who said that they had casual sexual partners were less likely to notify them (23) , confirming that success in this action is more common in cases involving steady relationships (24) . Analysis identified a higher probability of partners not coming to the health unit in the group of index patients who said that they used condoms in comparison with those who reported not using them at all, which corroborated a study that showed the existence of higher chances of notifying partners in patients who said that they had not used condoms in their last intercourse events when compared to those who said that they had used this protection alternative (16) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consequently, the data pointed to a higher probability of not getting casual sexual partners to come to the health unit, in comparison with that of noncasual ones. Similar results were described in a study on PR carried out in the United States, according to which patients who said that they had casual sexual partners were less likely to notify them (23) , confirming that success in this action is more common in cases involving steady relationships (24) . Analysis identified a higher probability of partners not coming to the health unit in the group of index patients who said that they used condoms in comparison with those who reported not using them at all, which corroborated a study that showed the existence of higher chances of notifying partners in patients who said that they had not used condoms in their last intercourse events when compared to those who said that they had used this protection alternative (16) .…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the correlation between success in getting sexual partners to come to the health unit and STI types (regardless of having more than one infection) or the way the diagnosis was obtained (syndromic, laboratory, or rapid tests), analysis showed no association with any of these variables, a fact that had been verified in another study (24) . However, these factors were pointed out as being able to influence the patient's decision regarding PR, especially if the case involves the presence of HIV, because of the chronic nature of the viral infection and the stigma associated with it (22) .…”
Section: Discussionmentioning
confidence: 80%
“…We found that both MSM and trans women perceived less social support for partner notification of an STI diagnosis (33.4% MSM SNM, 37.4% trans women SNM “completely in favor”) compared to other sexual health behaviors. This result may be situated within prior Peruvian literature, as previous work has found partner notification practices to vary with factors such as partnership type (in relation to perceived risks and benefits of notification as well as ability to contact partners), type of STI diagnosed (HIV or other STIs), perception of peer support for notification, and fear of rejection or interpersonal violence [ 29 31 ]. It is notable that participants reported low levels of HIV serostatus communication with sexual partners in a separate analysis from this same study cohort, as our finding regarding social support for partner STI notification may reflect broader reticence in sexual communication norms [ 23 ].…”
Section: Discussionmentioning
confidence: 66%
“…While the Peruvian Ministry of Health maintains detailed guidelines for managing sexual partners of individuals with syphilis (including provider counseling, distribution of referral cards, and home treatment visits for partners of pregnant women), these services are delivered inconsistently in practice [ 35 , 36 ]. The deficiencies of existing partner management systems in Peru can be seen in the findings from a previous study where after 1 year, only 41% of individuals with syphilis infection had notified any of their partners and 43% had been reinfected after the confirmation of cure [ 37 , 38 ]. We conducted a factorial, RCT to compare the effect of printed partner referral cards and/or access to a Web-based notification system against standard counseling on self-reported PN outcomes among MSM in Lima, Peru, with untreated syphilis infection.…”
Section: Introductionmentioning
confidence: 99%